Preliminary Analysis of Enrichment Media Based on Physics Edupark in Cave Tourism Destination - Tessa Destia Putri Lisa; Hamdi Rifai; Husna Husna; Pratiwi Ineke Anwar (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a preliminary research that aims to analyze the needs in developing enrichment media based on edupark physics in cave tourism destinations. The type of research used is the research and development using the Plomp model. This research is only a preliminary research phase which consists of teacher analysis, student analysis, and potential material analysis. The data used in this study were obtained from interviews and questionnaires given to physics teacher and 68 students from class X which is combined from SMAN 1 Lareh Sago Halaban and SMAN 2 Sijunjung students. Based on this preliminary research, the results show that media in video form has advantages for: motivating students to learn, showing physical phenomena as a whole, helping to develop student’s knowledge and skills, and helping students master the physics material. Besides that, cave tourism activities can be used as a physics edupark and as an object in developing physics edupark enrichment media in the form of videos because they have many connections with physics concepts. It can be concluded that multimedia interactive in the form of video is the most suitable learning media to be used as an enrichment media based on physics edupark.